Cholesterol-metabolizing enzyme cytochrome P450 46A1 as a pharmacologic target for Alzheimer's disease. (1st September 2017) - Mast, Natalia; Saadane, Aicha; Valencia-Olvera, Ana; Constans, James; Maxfield, Erin; Arakawa, Hiroyuki; Li, Young; Landreth, Gary; Pikuleva, Irina A.
Abstract: Cytochrome P450 46A1 (CYP46A1 or cholesterol 24-hydroxylase) controls cholesterol elimination from the brain and plays a role in higher order brain functions. Genetically enhanced CYP46A1 expression in mouse models of Alzheimer's disease mitigates the manifestations of this disease. We enhanced CYP46A1 activity pharmacologically by treating 5XFAD mice, a model of rapid amyloidogenesis, with a low dose of the anti -HIV medication efavirenz. Efavirenz was administered from 1 to 9 months of age, and mice were evaluated at specific time points. At one month of age, cholesterol homeostasis was already disturbed in the brain of 5XFAD mice. Nevertheless, efavirenz activated CYP46A1 and mouse cerebral cholesterol turnover during the first four months of administration. This treatment time also reduced amyloid burden and microglia activation in the cortex and subiculum of 5XFAD mice as well as protein levels of amyloid precursor protein and the expression of several genes involved in inflammatory response. However, mouse short-term memory and long-term spatial memory were impaired, whereas learning in the context-dependent fear test was improved. Additional four months of drug administration (a total of eight months of treatment) improved long-term spatial memory in the treated as compared to the untreated mice, further decreased amyloid-β content in 5XFAD brain, and also decreased the mortality rate among male mice. We propose a mechanistic model unifying the observed efavirenz effects. We suggest that CYP46A1 activation by efavirenz could be a new anti-Alzheimer's disease treatment and a tool to study and identify normal and pathological brain processes affected by cholesterol maintenance. Highlights: CYP46A1 activity was enhanced pharmacologically by the anti -HIV drug efavirenz. CYP46A1 activation promoted cholesterol turnover in the brain of 5XFAD mice. CYP46A1 activation reduced amyloid-β burden in the brain of 5XFAD mice. CYP46A1 activation reduced microglial immunoreactivity in the brain of 5XFAD mice. Efavirenz effects on behavior of 5XFAD mice were task- and treatment time-specific.